Case-Based Tutoring from a Medical Knowledge Base - Chin, Homer L. (1988)
The past decade has seen the emergence of programs that make use of large knowledge bases to assist physicians in diagnosis within the general field of internal medicine. One such program, Internist-I, contains knowledge about over 600 diseases, covering a significant proportion of internal medicine. This paper describes the process of converting a subset of this knowledge base--in the area of cardiovascular diseases--into a probabilistic format, and the use of this resulting knowledge base to teach medical diagnostic knowledge. The system (called KBSimulator--for Knowledge-Based patient Simulator) generates simulated patient cases and uses these cases as a focal point from which to teach medical knowledge. It interacts with the student in a mixed-initiative fashion, presenting patients for the student to diagnose, and allowing the student to obtain further information on his/her own initiative in the context of that patient case. The system scores the student, and uses these scores to form a rudimentary model of the student. This resulting model of the student is then used to direct the generation of subsequent patient cases. This project demonstrates the feasibility of building an intelligent, flexible instructional system that uses a knowledge base constructed primarily for medical diagnosis.